Development of Teaching Materials Short-Distance Running Athletics Based on Interactive Multimedia For Class VIII Junior High School Students - Herwindo Setyawan; Sunardi Sunardi; Deny Tri Ardianto (Universitas Sebelas Maret, 2021)
The development research carried out has a purpose of developing teaching materials based on interactive multimedia on physical education subjects for learning short distance running athletics. This study aims to determine the feasibility of these teaching materials as learning media, especially during the Covid-19 period. The method used in this research is a preliminary study survey with a descriptive approach to find out the initial data which is the process of developing teaching material products based on interactive multimedia and the instrument used is a questionnaire. The schools that were used as research samples were two Junior High School in Sukoharjo Regency with the subjects of this study 191 students. Based on a preliminary study survey with a questionnaire instrument for students in each school, who understand sprinting technique is 63.9% and 36.1% have not been able to fully understand. From the findings of the preliminary study survey with the questionnaire instrument in the two schools above, it shows that teachers and students from Junior High School in Sukoharjo Regency have a fairly good perception. Teaching materials based on interactive multimedia is learning that contain material, evaluation questions, videos, tutorials, and simulations. Interactive multimedia criteria include attractive and interactive design, usable, accessible, appropriate, relevant. Development of teaching materials based on interactive multimedia for learning short-distance running athletic as an alternative to learning during the Covid-19 pandemic that is suitable for use in teaching and learning activities.